(untitled) (Journal of Pathology of Nepal, 2017)
Background: Ovarian cysts, which present as neoplastic and non-neoplastic lesions, are the most common gynecological cause of hospital admissions. This study was conducted to know the spectrum of ovarian tumors. Materials and methods: A cross sectional study was carried out among all the ovarian specimens sent for histopathological examination. Results: Forty two cases were Surface epithelial tumours and 49 cases were germ cell tumour. Among Surface epithelial tumours, 34 (80.95%) were benign neoplasm, 2(4.76%) were borderline and 6 including one Krukenberg tumour (14.29%) were malignant neoplasm. Among all Germ cell tumours, 45 (91.84%) were Mature cystic teratoma, 1 (4.08%) was Immature cystic teratoma and 2 (4.08%) were Dysgerminoma. Conclusion: Incidence of Surface epithelial tumours and germ cell tumours were found to be almost equal with mild predominance of Germ cell tumour.